Age-Related Changes in Egg Quality of Hy-Line Brown Hens - Kim, Chang-Ho; Song, Jong-Ho; Lee, Jae-Cheong; Lee , Kyung-Woo (International Journal of Poultry Science, 2014)
The present study was conducted to monitor age-related changes in egg quality during the entire production cycle of laying hens. Thirty eggs were sampled from the commercial farm on a weekly basis for egg analysis. In order to increase in confidence in sampling, farm personnel were educated to collect the eggs from the pre-determined cages during the whole period and all layers were subjected to an identical farm management and fed a commercial layer diet. In total, 1,470 eggs were sampled and transported to the laboratory of Korea Institute for Animal Products Quality Evaluation. The parameters for egg quality included egg weight, eggshell color, eggshell breaking strength, eggshell thickness, Haugh unit and yolk color. It was shown that egg weight increased as the hen aged. Eggshell breaking strength gradually decreased, but eggshell thickness was randomly scattered without showing any age-related trends during the laying period. The intensity of eggshell color kept relatively constant while yolk color increased with age. Finally, Haugh unit as an indicator of freshness of eggs was consistently decreased as the hens aged. In this study, we noticed that eggshell breaking strength and egg weight were negatively correlated (r= - 0.500, p0.50), but marginally and positively correlated with egg weight (r = 0.248, p = 0.082). It is concluded that among the various egg quality parameters analyzed, egg weight, eggshell breaking strength or Haugh unit reduced as the hens aged. Further study is needed to include various parameters of egg quality such as chemical or nutritional composition which will provide more insight into the age-mediated changes in egg quality.